Integration of Veteran Students into the Country’s Educational Environment: the Experience of the United States of America - Batyuk, Liliya (Pedagogical Discourse, 2025)
The development of STEM education in Ukraine, the formation of a balanced policy in the country’s educational space under martial law, and the creation of a favorable educational environment for military personnel upon returning from military service to civilian life are defined in a number of regulatory acts and laws set out on the official website of the Government of Ukraine, on the website of the Ministry of Education and Science of Ukraine, and on the websites of other government institutions. In the new realities of Ukraine today, the return of military personnel to civilian life requires new jobs, which is a consequence of mastering new modern in-demand professions, which in turn are a consequence of obtaining modern STEM education. In this sense, the experience of the United States of America can be useful for Ukraine to develop an educational environment and educational reforms that meet the needs of the state. As a result of the theoretical and methodological analysis, based on research in the field of pedagogical education, philosophy and management, the directions of reforms of the United States Government aimed at supporting student veterans in the context of obtaining higher education in the second half of the 20th - first half of the 21st century were analyzed; the system of forming professional competence of future specialists from among student veterans of the war in higher education institutions was considered; the main problems faced by military personnel when entering higher education institutions were identified; the level of awareness, experience of use and satisfaction with state programs and benefits aimed at supporting student veterans and their families was clarified. Given the need for a unified and comprehensive policy of integrating veterans into the public life of the country, the USA proposed a conceptual model that takes into account the multifaceted integration of veterans, including the opportunities to obtain higher, and any other STEM education, in better quality. Effective veteran integration policies contribute to the United States’ progress toward achieving specific national sustainable development goals, including STEM education for all.